Character Building of Students Through Edupreneurship in Islamic Boarding Schools (Case Study of Class XII MA Al-Amien 1 Pragaan) - Istianatul Mabruhah; Najmi Faza (Penerbit Presisi Pustaka, 2025)
Edupreneurship is entrepreneurship education implemented in creative and innovative businesses in Islamic boarding schools (pesantren) to prepare students to become mentally and materially independent in facing life after graduation. The research questions addressed in this study are: 1. What strategies are implemented in Islamic boarding schools to develop students' edupreneurial character? 2. What are the impacts of edupreneurial character building in these Islamic boarding schools? This research was designed using a qualitative approach with a case study approach. Data collection techniques included observation, interviews, and documentation. The results found that edupreneurial character building is carried out through systematic strategies, such as instilling Islamic entrepreneurial principles, structured learning oriented toward character values, implementing learning-by-project methods, providing motivation and future direction, and creating an interactive and enjoyable learning environment. These strategies have proven effective in fostering honesty, responsibility, hard work, creativity, independence, and leadership among students. The tangible impact of this program's implementation is evident in students' increased economic independence, innovative thinking skills, mature future planning, and high self-confidence.